HEMORRHAGIC DISEASE OF THE NEWBORN (Multidisciplinary Journal of Science and Technology, 2025)
The article discusses the problems of hemorrhagic disease of newborns with late debut. Currently, hemorrhagic disease prevention is not carried out for all newborns in maternity hospitals. A clinical analysis of 9 cases of the disease was conducted. A dangerous feature of the late manifestation of hemorrhagic disease (after a month of life) is the development of massive intracranial hemorrhages against the background of increased bleeding.